Characterization of Hyaluronidase 4 Involved in the Catabolism of Chondroitin Sulfate - Shuhei Yamada; Shuji Mizumoto (Molecules, 2022)
Hyaluronidases (HYALs) are endo-beta-N-acetylhexosaminidases that depolymerize not only hyaluronan but also chondroitin sulfate (CS) at the initial step of their catabolism. Although HYAL1 hydrolyzes both CS and HA, HYAL4 is a CS-specific endoglycosidase. The substrate specificity of HYAL4 and identification of amino acid residues required for its enzymatic activity have been reported. In this study, we characterized the properties of HYAL4 including the expression levels in various tissues, cellular localization, and effects of its overexpression on intracellular CS catabolism, using cultured cells as well as mouse tissues. Hyal4 mRNA and HYAL4 protein were demonstrated to be ubiquitously expressed in various organs in the mouse. HYAL4 protein was shown to be present both on cell surfaces as well as in lysosomes of rat skeletal muscle myoblasts, L6 cells. Overexpression of HYAL4 in Chinese hamster ovary cells decreased in the total amount of CS, suggesting its involvement in the cellular catabolism of CS. In conclusion, HYAL4 may be widely distributed and play various biological roles, including the intracellular depolymerization of CS.